Academic monitoring in the perception of nursing students - Cinthya das Neves Burgos; Crysthianne Cônsolo de Almeida Baricati; Júlia Trevisan Martins; Alessandro Rolim Scholze; Maria José Quina Galdino; Marcia Eiko Karino (Universidade Federal de Santa Maria, 2019)
Aim: to know the perception of nursing students regarding the academic monitoring practice performed in a laboratory of nursing techniques simulation. Method: qualitative study, developed with 18 monitors, between November and December 2017, through semi-structured interview. The data was analyzed by the technique of content analysis. Results: the participants indicated monitoring as an awakening for teaching, exchange of experience among them, improvement in interpersonal relations, moment to remember what they had learned in theory, encouragement to study and strengthening of the student and teacher relationship. Final considerations: monitoring has been an important tool for the development of theoretical-practical skills, which are important for personal and professional growth.